Minority language, majority canon - Hill, Sarah (Popular Music History, 2013)
In this article I explore the idea of ‘canon’ in a lesser spoken language culture. The sense of ‘canon’ in Welsh popular music is intimately related to political and cultural activity, and ‘canonical’ figures are often inseparable from their involvement in the movement to secure a future for the Welsh language. By examining the relationship between the Anglo-American ‘majority’ canon and its ‘minority’ Welsh counterpart, I engage with the process of historicizing Welsh popular music on its own musical and chronological terms as but one in a possible network of ‘microcanons’ that exist to challenge Anglo-American cultural dominance.